ANALISISPENGARUH PEMBIAYAAN MURABAHAH TERHADAP OMZET UMKM (STUDI KASUS PADA PT BPRS HARTA INSAN KARIMAH CABANG CIKARANG) - Erisma Venny Mursidah; Rafika Rahmawati; Arief Widyananto (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This study aims to analyze the effect of murabahah financing at BPRS Harta Insan Karimah Cabang Cikarang branch on changes in turnover of micro, small and medium enterprises and to find out how big the difference in customer turnover before and after receiving murabahah financing. The research methodology used is a quantitative approach. The sampel used is micro, small and medium-sized financing customers of BPRS Harta Insan Karimah Cabang Cikarang branch in 2018 as many as 70 respondents with various types of businesses. The results of this study indicate that partial murabahah financing has a positive and significant effect between the variables of murabahah financing on micro, small and medium enterprises turnover